State of mobile crowdsourcing applications: A review - Mahmud F.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Big data; Computer software; Industrial research; Information dissemination; Mobile devices; Software engineering; Current situation; Information distributions; Mobile crowdsourcing; secondary study; Systematic literature review; Systematic Review; Crowdsourcing